Effect of solid fraction on the mechanical properties of thixomolded magnesium alloys - Goryany V.; Mauk P.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The higher the fraction of solid phase in the partly solidified melt during pouring, the poorer the mechanical properties of thixocast components. The solid fraction decreases as the pouring temperature rises. Recommended temperature profiles for the pouring cylinder are shown. The flow characteristics of the partly solidified melt hardly changes as the content of solid matter increases.